Synapse Pathology in Schizophrenia: A Meta-analysis of Postsynaptic Elements in Postmortem Brain Studies - Berdenis van Berlekom, Amber (Schizophr Bull, 2020)
Changed synapse density has been suggested to be involved in the altered brain connectivity underlying schizophrenia (SCZ) pathology. However, postmortem studies addressing this topic are heterogeneous and it is not known whether changes are restricted to specific brain regions. Using meta-analysis, we systematically and quantitatively reviewed literature on the density of postsynaptic elements in postmortem brain tissue of patients with SCZ compared to healthy controls. We included 3 outcome measurements for postsynaptic elements: dendritic spine density (DSD), postsynaptic density (PSD) number, and PSD protein expression levels. Random-effects meta-analysis (31 studies) revealed an overall decrease in density of postsynaptic elements in SCZ (Hedges’s g: −0.33; 95% CI: −0.60 to −0.05; P = .020). Subgroup analyses showed reduction of postsynaptic elements in cortical but not subcortical tissues (Hedges’s g: −0.44; 95% CI: −0.76 to −0.12; P = .008, Hedges’s g: −0.11; 95% CI: −0.54 to 0.35; P = .671) and specifically a decrease for the outcome measure DSD (Hedges’s g: −0.81; 95% CI: −1.37 to −0.26; P = .004). Further exploratory analyses showed a significant decrease of postsynaptic elements in the prefrontal cortex and cortical layer 3. In all analyses, substantial heterogeneity was present. Meta-regression analyses showed no influence of age, sex, postmortem interval, or brain bank on the effect size. This meta-analysis shows a region-specific decrease in the density of postsynaptic elements in SCZ. This phenotype provides an important cellular hallmark for future preclinical and neuropathological research in order to increase our understanding of brain dysconnectivity in SCZ.